2010
DOI: 10.1107/s0021889810043955
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and experimental developments for accurate determination of crystallinity of cellulose I materials

Abstract: This work defines the crystallinity of cellulose I materials on a dry‐weight basis. Theoretical and experimental developments in X‐ray diffraction lead to a crystallinity determination method that is estimated to reach 1σ accuracies of better than 0.05 (crystallinity defined between 0 and 1). The method is based on Rietveld modelling, to resolve cellulose I Bragg peaks, and a standard truncated invariant integral. Corrections are derived to account for incoherent scattering, moisture content and other composit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
87
0
6

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(95 citation statements)
references
References 24 publications
2
87
0
6
Order By: Relevance
“…Note that most of the methods incorrectly assume that X-ray sensitivity to crystalline and amorphous phases is the same. The Rietveld fitting of XRD data can resolve these uncertainties in the CI calculation [45]. Because these advanced methods are not easily amenable to non-XRD experts, a more user-friendly method has been developed [46].…”
Section: Correlation Of "Apparent" Crystallinity Estimated From Xrd mentioning
confidence: 99%
“…Note that most of the methods incorrectly assume that X-ray sensitivity to crystalline and amorphous phases is the same. The Rietveld fitting of XRD data can resolve these uncertainties in the CI calculation [45]. Because these advanced methods are not easily amenable to non-XRD experts, a more user-friendly method has been developed [46].…”
Section: Correlation Of "Apparent" Crystallinity Estimated From Xrd mentioning
confidence: 99%
“…The traditional cellulose model describes cellulose chains as containing ordered, crystalline and amorphous (less ordered) regions. The X-ray diffraction method considers the contributions from crystalline and amorphous cellulose to the entire XRD spectra and is generally regarded an accurate technique of the crystallinity index measurement, although the crystallinity values obtained by this method may be higher than those obtained by the other methods (Park et al 2010;Cao and Tan 2005;Driemeier and Calligaris 2011). The X-ray diffractograms of the seven kraft pulps, which were produced as described above, suggested the presence of amorphous and crystalline regions.…”
Section: Characterization Of Cellulosic Pulpsmentioning
confidence: 99%
“…Largely XRD is reported and the Rietveld refinement is commonly considered to be the most accurate method. 97 In a recent publication however, Ahvenainen et al found good correlation with the five most common XRD fitting methods and the two dimensional Rietveld method. 98 Moreover, within their work it is emphasized that comparison between samples and laboratories is extremely challenging.…”
Section: Blue Goose Biorefineriesmentioning
confidence: 99%